Enhancing Environmental Awareness in Elementary Students Through 3R Education: Implementation and Impact at SDN 6 Padang Sambian Klod: English - Komang Widhya Sedana Putra P; I Gusti Ayu Agung Mirah Virgianitri; Ni Wayan Lasmi; Wayan Sri Maitri (NEAR: Jurnal Pengabdian kepada Masyarakat, 2025)
This Community Service Program seeks to improve students' caring attitudes towards the environment at SDN 6 Padang Sambian Klod through the application of the 3R (Reduce, Reuse, Recycle) concept. The main problem in focus is the student’s low level of knowledge and participation in appropriate waste disposal activities which results in pollution of the environment. This problem is solved through direct observation, counseling, discussions, and practical work including waste sorting and recycling workshops. The students’ improved awareness and behavior is profound. More than eighty percent of students have shown improvement in waste management understanding, practiced waste segregation, and recycling. Teachers and parents also noted that students were actively participating in cleanliness activities at school and at home. Even so, there are still problems such as a greater proportion of these facilities need to be provided and sustained waste management practices need to be more deeply entrenched. The conclusions drawn are that further education and better facilities would help children develop better environmental attitudes.